Analysis of T-Shirt Product Quality Control to Minimize Defects Using Fault Tree Analysis (FTA) and Failure Mode and Effects Analysis (FMEA) at CV Dwiputra Ihwa - Rifal Choerul Harisin; Rizky Fajar Ramdhani; Akhsani Nur Amalia (Global Writing Academica Researching and Publishing, 2026)
CV Dwiputra Ihwa is a company that operates in the garment industry, specifically producing T-shirts based on special orders or in large quantities. From June 2025 to May 2026, the percentage of defective products was 7.6% out of a total production of 18,478 units. This situation leads to more rework, waste of raw materials, and lower production efficiency. This study aims to find out which type of defect is most common, look into why these defects happen, and figure out what improvements should be done first to make the T-shirt product better. The study uses a descriptive method with a qualitative approach through a case study. Data was collected through observation, interviews, and document study, then analyzed using Pareto Diagram, Fault Tree Analysis, and Failure Mode and Effect Analysis. The Pareto chart analysis shows that stitching defects (43%) and inaccurate screen-printing defects (37%) are the two main types of defects, contributing about 80% of all defective products. The FTA analysis shows that the second type of defect is caused by a combination of human factors, methods, materials, and machines (4M), with human factors and methods being the most significant causes. The FMEA analysis results show that the Risk Priority Number (RPN) ranges from 30 to 252, with the highest risk cause being overly high production targets (RPN = 252). Based on the research results, it can be concluded that using Pareto Diagram, FTA, and FMEA is effective in identifying types of defects, analyzing root causes, and determining priorities for improvement, which helps support the enhancement of the quality of T-shirts produced by CV Dwiputra Ihwa.